A Bifactor Model of Subjective Well-Being at Personal, Community, and Country Levels: A Case With Three Latin-American Countries - Torres-Vallejos, Javier; Juarros-Basterretxea, Joel; Oyanedel, Juan Carlos; Sato, Masatoshi (Frontiers in Psychology, 2021)
Improving citizen's subjective well-being (SWB) has become an increasingly visible policy goal across industrialized countries. Although an increasing number of studies on SWB has been developed at the individual level, little is known about subjective evaluation at social levels, such as the community and national levels. While the relationships between these levels have been analyzed, it is essential to consider whether these assessments are part of the same unique construct of subjective well-being. The purpose of this study was to examine the dimensionality and reliability of a single measure of SWB, which contain individual, community, and national level, across three Latin-American countries, using a bifactor model analysis. Findings showed that the bifactor model exhibited a good fit to the data for the three countries. However, invariance testing between countries was not fully supported because of each item's specific contribution to both specific and general constructs. When analyzing these models separately for each country, it is observed that the SWB construct is in a gray area between unidimensionality and multidimensionality, since some factors contribute more to the general factor and others to the specific level, depending on the country. These findings call for integrating more distant levels (community and country levels) into the tradition of evaluating SWB at the individual level, as they contribute not only to an overall construct, but make individual contributions to it, which must be considered in terms of public policy.